A233 AGING AND ESOPHAGEAL MOTILITY: A HIGH-RESOLUTION MANOMETRY STUDY. (4th March 2021) - Djinbachian, R; Marchand, E; Yan, W; Bouin, M
Abstract: Background: Studies have found possible physiologic changes to esophageal motility with aging that are not currently taken into account in routine high-definition esophageal manometry (HDEM) interpretation. Aims: We aimed to quantify the relationship between these physiologic changes and aging to improve HDEM interpretation. Methods: We conducted a retrospective analysis of medical records for all patients who underwent HDEM at a tertiary hospital center between January 2015 and December 2019. Inclusion criteria were patients ≥18 years with normal HDEM. Exclusion criteria were abnormal HDEM; abnormal upper digestive endoscopy or imagery. Outcomes were median integrated relaxation pressure (IRP); mean lower esophageal sphincter (LES) pressure; mean distal contractal integral (DCI); mean distal latency (DL); mean peristaltic break (PB) according to the v3.0 Chicago classification criteria. Data was extracted from electronic patient medical records into a database for analysis. Effect of age on outcomes was examined through univariate and multivariate linear regression analysis. Results: We identified 1917 patients with HDEM and included 790 patients with normal exams [mean age 55.8 yrs (IQR 46 – 66), 64% female]. Indications for HDEM included dysphagia (41.3%); gastroesophageal reflux disease (29.2%); chest pain (11.0%); other (13.3%). There was a statistically significant relationship between age and IRP [Coef=0.08 (95%CI 0.05 – 0.1), p<0.001, R^2=0.04] as well as DCI [Coef=10.9 (95%CI 4.1 – 17.8), p=0.002, R^2=0.01] and DL [Coef=-0.01 (95%CI -0.02 – -0.002), p=0.01, R^2=0.008]. No statistically significant relationship was found between age and LES pressure [Coef=0.03 (95%CI -0.01 – 0.08), p=0.16] or PB [Coef=0.007 (95%CI -0.002 – 0.016), p=0.14]. Multivariate analysis showed statistically significant relationships between IRP and age (p<0.001), BMI (p=0.001), NSAID use (p=0.034), and female sex (p=0.048). Conclusions: We found that IRP, DCI, and DL are significantly correlated with the normal aging process. Modifications could therefore be considered for normal diagnostic cutoffs for both age extremes to prevent over or under-diagnosis of motility disorders. Funding Agencies: None